Building brands through mobile-enhanced communities - Wang, Alex (Henry Stewart Talks, 2009)
What is cross-media integration?, How to build brands through cross-media integration, Essential strategies, Evidence of using cross-media integration in the mobile marketing environment, Applications of using cross-media integration in building brands in the mobile marketing environment
Archived at 2022/04/11